Distinct RBC alloantibody responses in type 1 interferon-dependent and -independent lupus mouse models - Paul, Kausik; Hernández-Armengol, Rosario; Lee, June Young; Chang, Che-Yu; Shibata, Tomohiro; Yamashita, Michifumi; Jefferies, Caroline; Gibb, David R. (Frontiers in Immunology, 2024)
During transfusion of red blood cells (RBCs), recipients are exposed to both ABO and non-ABO ‘minor’ antigens. RBC donor units and recipient RBCs are not routinely matched for non-ABO antigens. Thus, recipients are exposed to many RBC alloantigens that can lead to RBC alloantibody production and subsequent clinically significant hemolysis. RBC alloantibodies also significantly limit the provision of compatible RBC units for recipients. Prior studies indicate that the frequency of RBC alloimmunization is increased during inflammatory responses and in patients with autoimmune diseases. Still, mechanisms contributing to alloimmune responses in patients with autoimmunity are not well understood. More than half of adult patients with systemic lupus erythematosus (SLE) produce type 1 interferons (IFNα/β) and express IFNα/β stimulated genes (ISGs). Previously, we reported that IFNα/β promote RBC alloimmune responses in the pristane mouse model, which develops a lupus-like phenotype that is dependent on IFNα/β signaling. However, it is unclear whether IFNα/β or the lupus-like phenotype induces alloimmunization in lupus models. Therefore, we tested the hypothesis that IFNα/β promotes RBC alloimmune responses in lupus by examining alloimmune responses in IFNα/β-independent (MRL-lpr) and IFNα/β-dependent (pristane) lupus models. Whereas pristane treatment significantly induced interferon-stimulated genes (ISGs), MRL-lpr mice produced significantly lower levels that were comparable to levels in untreated WT mice. Transfusion of murine RBCs that express the KEL antigen led to anti-KEL IgG production by pristane-treated WT mice. However, MRL-lpr mice produced minimal levels of anti-KEL IgG. Treatment of MRL-lpr mice with recombinant IFNα significantly enhanced alloimmunization. Collectively, results indicate that a lupus-like phenotype in pre-clinical models is not sufficient to induce RBC alloantibody production, and IFNα/β gene signatures may be responsible for RBC alloimmune responses in lupus mouse models. If these findings are extended to alternate pre-clinical models and clinical studies, patients with SLE who express an IFNα/β gene signature may have an increased risk of developing RBC alloantibodies and may benefit from more personalized transfusion protocols.